Nicaragua : Promoting Competitiveness and Stimulating Broad-based Growth in Agriculture - World Bank (Washington, DC, 2013)
The report argues that Nicaragua's best hope for sustained growth, and poverty reduction, probably lies with agricultural exports, which have the potential to gain from opportunities in world markets. Despite the small share of farmland devoted to the production of exports (25 percent of harvested area), the total trade of agricultural goods (including the value of both imports, and exports) accounted for almost eighty five percent of agricultural GDP in 1998. This is high relative to several countries in the area. But most likely, the most promising is the export performance of non-traditional agricultural products. The report accords greatest emphasis to improving competitiveness, and recommends giving this goal highest priority. To this end, four areas for action to improve competitiveness have bee identified: modernizing agribusiness; promoting agricultural exports; improving the effectiveness of public spending; and, strengthening public-private partnerships. These measures will also have to be complemented by sustained, ongoing efforts to improve factor market efficiency, suggesting improvements to facilitate rural finance; boost access to technology, improve land productivity, and, raise labor market's human capital. In addition, the significant risks faced by the country's agricultural sector - natural disasters and economic shocks - call for improved agricultural risk management, through innovative insurance products, and credit services, as well as improved warning systems to forecast weather related disasters.